Terahertz magneto-optical properties of bi- and tri-layer graphene. (6th April 2018) - Mei, Hongying; Xu, Wen; Wang, Chao; Yuan, Haifeng; Zhang, Chao; Ding, Lan; Zhang, Jin; Deng, Chao; Wang, Yifan; Peeters, Francois M
Abstract: Magneto-optical (MO) properties of bi- and tri-layer graphene are investigated utilizing terahertz time-domain spectroscopy (THz TDS) in the presence of a strong magnetic field at room-temperature. In the Faraday configuration and applying optical polarization measurements, we measure the real and imaginary parts of the longitudinal and transverse MO conductivities of different graphene samples. The obtained experimental data fits very well with the classical MO Drude formula. Thus, we are able to obtain the key sample and material parameters of bi- and tri-layer graphene, such as the electron effective mass, the electronic relaxation time and the electron density. It is found that in high magnetic fields the electronic relaxation time τ for bi- and tri-layer graphene increases with magnetic field B roughly in a form τ ∼ B 2 . Most importantly, we obtain the electron effective mass for bi- and tri-layer graphene at room-temperature under non-resonant conditions. This work shows how the advanced THz MO techniques can be applied for the investigation into fundamental physics properties of atomically thin 2D electronic systems.